Polymeric biomaterials inspired by marine mussel adhesive proteins - Vale, A. Catarina (2021)
Marine mussels have attracted attention in the last years due to their incredible ability to stick to various organic and inorganic substrates in harsh environments. This capacity has been attributed to specific proteins secreted by marine mussels, known as marine mussel adhesive proteins (MAPs). These proteins have in their constitution an unusual amino acid, 3,4-dihydroxyphenylalanine (DOPA). Many efforts have been made to produce materials with adhesive properties equivalent to those shown by MAPs for biomedical applications. Therefore, distinct polymeric biomaterials, either with two-dimensional or three-dimensional structures, have been developed trying to mimic this incredible adhesive performance. In this review, an overview of the application of MAPs and their adhesive properties on the development of distinct biomaterials based on both natural and synthetic polymers will be presented, namely on films and hydrogels production. The variety of biomedical applications of these bioinspired materials will be also discussed.